Coloured Urban Landmarks in Tirana: Impact on Life Quality and Socioeconomic Costs - Divya, Srimitha (Journal of Progress in Civil Engineering, 2025)
As many post‐communist cities, Tirana presents its visitors with soviet style buildings/concrete ‐ apartment blocks. These buildings were a solution for the housing problem in the city. This paper aims to analyse the relationship between these blocks, their inhabitants, and the city. Multi‐storey buildings are a form of identity loss for their inhabitants but in meantime it has opened a new window of opportunity in the real estate market in Albania. Once again, architecture, even on the slightest side of it connects people immensely with their everyday affairs.